CORRELATION BETWEEN ACNE VULGARIS SEVERITY AND QUALITY OF LIFE AMONG UNJANI MEDICAL STUDENTS - Hedi Hendrawan Rachmatdinata; Welly Ratwita; Narita Ratukuri Paradila (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2026)
Acne vulgaris (AV) is a chronic inflammatory skin disease that commonly affects adolescents and young adults. Medical students are particularly susceptible to AV because of the academic demands and psychological stress they experience. In addition to its physical manifestations, AV can negatively affect psychological and social aspects, potentially reducing quality of life. This study aimed to identify and analyze the correlation between the severity of AV and the quality of life of undergraduate medical students at Jenderal Achmad Yani University (Unjani) from the Class of 2023. This analytical study employed a cross-sectional design. A total of 66 students were selected using consecutive sampling. The severity of acne vulgaris was assessed based on facial photographs evaluated by a dermatologist. Quality of life was measured using the Cardiff Acne Disability Index (CADI) questionnaire. Data were analyzed using Spearman’s correlation test. Most respondents had mild acne (65.2%) and reported mild impairment in quality of life (51%). The analysis revealed a significant strong positive correlation between acne severity and impairment of quality of life (p = 0.000; r = 0.764). Increased acne severity was associated with greater impairment of quality of life. These findings indicate that the more severe acne is associated with greater psychological and social disturbances. Keywords: acne vulgaris, medical students, quality of life DOI 10.35990/mk.v9n2.p197-209